GREEN FINANCE: WAYS TO ATTRACT SUSTAINABLE INVESTMENTS (International scientific-electronic journal “Pioneering studies and theories”, 2025)
Green finance is a crucial tool for ensuring sustainable economic growth and environmental stability. This article analyzes green financing instruments, including green bonds, the role of green banks, and the significance of ESG (Environmental, Social, and Governance) investments. The study identifies effective methods for attracting sustainable investments and discusses global experiences in green finance.
Keywords: ESG investments; green finance; sustainable economy; green banks; green bonds